Bioactive glass in the treatment of chronic osteomyelitis—a valid option?. Issue 3 (15th June 2021) - Ziegenhain, Franziska; Neuhaus, Valentin; Pape, Hans-Christoph
Abstract : Abstract: Chronic osteomyelitis continues to represent a challenge both for patients and the treating physician, especially in the presence of multiple germs. We performed a literature review assessing the current role of the indications of bioactive glass. We included studies about patients with chronic osteomyelitis that were treated with S53P4. A literature review of Medline via PubMed was performed. After the exclusion of case reports, 7 studies were included in the narrative review. Recurrence of infection was defined as the main outcome parameter. Six of 7 studies were retrospective, or case studies with a relatively small sample size (total patient number N = 274). The overall recurrence rate was 10.6%. Studies that compared the outcome of the treatment with S53P4 versus antibiotic-loaded polymethyl methacrylate (PMMA) revealed no significant difference. The data reviewed indicate that in cases of multiple bacteria and resistance to antibiotic treatment, bioglass may be a valuable treatment alternative to other forms of spacers (e.g., PMMA). This statement is limited by the fact that the number of described cases is very low. Therefore, a definitive statement of its effectiveness cannot be made at this point.